Reformulating reformulation: A technical appraisal and policy context for the 2019 FDI report on the impact of ultra-processed food reformulation in Ireland - Norah Campbell; Kathryn Reilly; Marius Claudy; Francis Finucane (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2019)
The food and beverage industry is beginning to focus on product reformulation as its key strategy to tackle obesity, and resource itself accordingly. In February 2019, Food Drink Ireland (FDI) launched a report ostensibly describing improvements in population-level dietary patterns in Ireland that resulted from industry-led reformulation initiatives. We sought to conduct a rigorous, objective assessment of this report. We found that it contains six fundamental flaws: it infers a causal relationship betweenindustry-led food reformulation and decreases in sugar, salt, saturated fat and energy intake; it selectively uses points of time and products, which leads to a high risk of selection bias; it blurs the difference between a marketing research report and ascientific report; it aggregates decreases in salt, sugar and saturated fats across categories and this masks the uneven nature of reformulation strategies; it introduces a status quo bias, normalizing the 2005 starting point; and it assumes that any progress in dietary change was solely as a result of industry voluntarism, demoting the work of public health and government policy. We think it is important that the limitations and weaknesses in the report are brought to the attention of the National Clinical Programme for Obesity and the Department of Health. We have provided a brief synopsis of international peer-reviewed research on industry-led reformulation strategies and consider the policy implications for the Irish Government.
Keywords: 330